2021
DOI: 10.1021/acsanm.1c02850
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot-Passivated Perovskite/Carbon Electrodes for Stable Solar Cells

Abstract: Carbon-based perovskite solar cells (C-PSCs) have been extensively researched as alternatives to fabricate cost-effective energy conversion devices. The interface of the perovskite film and the carbon electrode is crucial for achieving good photovoltaic performance. Herein, two carbon quantum dots (CQDs) with different functional groups designated as A-CQDs and CA-CQDs are used to passivate the perovskite CH3NH3PbI3 surface, respectively. The surface ligand effect arising from the two CQDs is extensively inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In addition, PSCs are suffering from significant non-radiative recombination losses originated from defect states of perovskites. Until now, numerous passivating strategies including solvent, composition, and interfacial engineering have been developed to enhance both efficiency and long-term stability. Specially, the buried interface between the perovskite layer and the underlying transport layer has been vastly investigated to minimize trap states and recombination losses as well as facilitate carrier extraction. For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. , Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk . Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSCs are suffering from significant non-radiative recombination losses originated from defect states of perovskites. Until now, numerous passivating strategies including solvent, composition, and interfacial engineering have been developed to enhance both efficiency and long-term stability. Specially, the buried interface between the perovskite layer and the underlying transport layer has been vastly investigated to minimize trap states and recombination losses as well as facilitate carrier extraction. For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. , Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk . Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that passivation with strong interaction energy promotes effective defect passivation, and inhibits defect migration as well . A surface passivation agent not only can passivate surface defects of perovskite, it can also be applied as an interfacial modifier to reduce energy level mismatching between perovskite and the carbon electrode. , Our group previously reported a 2-amino-5-(trifluoromethyl)­pyridine (5-TFMAP) passivation agent with bidentate groups to passivate the perovskite CH 3 NH 3 PbI 3 films . The two anchoring sites of a NH 2 group and a pyridine ring provided strong interaction with the undercoordinated Pb 2+ , efficiently reducing the defect states of perovskite films, promoting better carrier transport and inhibiting nonradiative recombination.…”
mentioning
confidence: 99%
“…Furthermore, CQD‐based C–PSCs retain more than 80% of their initial PCE under testing conditions of 35% humidity and 840 h of storage. [ 181 ] Figure 10 summarizes the fabrication procedure and shows transmission electron microscopy (TEM) and high‐resolution transmission electron microscopy images of A‐CQDs and the J–V characteristics.…”
Section: Carbonaceous Materials Applied To C–pscsmentioning
confidence: 99%